SUPPORTIVE THERAPY WITH IMMUNOMODULATORS FOR RHINITIS CASES IN DOMESTIC CATS - Ahmad Anang Intan Purnama Negara; Putu Devi Jayanti; I Gusti Made Krisna Erawan (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Supportive therapy using immunomodulators is one of the therapeutic options that can be used to increase or restore the balance of the body's immune system. The upper respiratory tract disease that often occurs in cats is rhinitis. This article aims to describe the incidence of rhinitis due to bacterial infection in local cats, a series of examinations to determine the diagnosis, and supportive therapy given using immunomodulators. The examinations carried out were physical examination, routine hematology, radiography, cytology, isolation and identification of bacteria and fungi. The results of the physical examination of the case cat found serous discharge coming out of the nose, and occasional sneezing followed by the release of serous discharge. The right mandibular lymph node was swollen. Seven days later the discharge turned purulent. The results of routine hematology examination showed that the case cat had leukocytosis. The results of the cytology of the case cat found a lot of neutrophil inflammatory cell infiltration. The results of the isolation and identification of bacteria and fungi with samples of the case cat's nasal discharge showed the presence of Enterococcus sp. Based on the anamnesis, physical examination, and laboratory examination, the cat was diagnosed with rhinitis with a fausta prognosis. The therapy given was cefixime (10 mg/kg BW) orally twice a day for 7 days, methylprednosolone (2 mg/kg BW) once a day for 4 days, and supportive therapy was also given, namely 4life Transfer factor Plus Tri Factor®Formula once a day for 7 days giving good results. On the seventh day, there was no discharge coming out of the nose and sneezing was no longer occurring. It is necessary to educate the owners of cats in cases about the importance of providing early rhinitis treatment so that the infection does not continue to worsen.